Influence of the particle size distribution of mineral filler on the physico-mechanical properties of block copolymers - V. M. Komarov; D. A. Zhizhimov (Тонкие химические технологии)
The mineral filler dispersity is shown to affect significantly the adsorption and strength properties of diene-styrene copolymers. Expressions for combinatorial entropy of mixing non-interacting particles in a multicomponent system were obtained, taking into account the contribution due to the difference in component size.